Adsorption of CTAB on Sapphire- c at High pH: Surface and Zeta Potential Measurements Combined with Sum-Frequency and Second-Harmonic Generation. - Abdelmonem, Ahmed; Zhang, Yingchun; Braunschweig, Björn; Glikman, Dana; Rumpel, Armin; Peukert, Wolfgang; Begovic, Tajana; Liu, Xiandong; Lützenkirchen, Johannes (Langmuir, 2022)
The adsorption of cetyltrimethylammonium bromide (CTA+Br-) on sapphire-c surfaces was studied at pH 10 below the surfactants' critical micelle concentration. The evolution of interfacial potentials as a function of CTAB concentration was characterized by surface and zeta potential measurements and complemented by molecular dynamic (MD) simulations as well as by second-harmonic (SHG) and vibrational sum-frequency generation (SFG) spectroscopy. The changes in interfacial potentials suggest that the negative interfacial charge due to deprotonated surface aluminols groups is neutralized and can be even overcompensated by the presence of CTA+ cations at the interface. However, SFG intensities from strongly hydrogen-bonded interfacial water molecules as well as SHG intensities decrease with both increasing CTAB concentration and the magnitude of the surface potential. They do not suggest a charge reversal at the interface, while the change in zeta potential is actually consistent with an apparent charge inversion. This can be qualitatively explained by results from MD simulation, which reveal adsorbed CTA+ cations outside a first strongly bound hydration layer of water molecules, where they can locally distort the structural order and replace some of the interfacial water molecules adjacent to the first layer. This is proposed to be the origin for the significant loss in SFG and SHG intensities with increasing CTAB concentration. Moreover, we propose that CTA+ can act as a counterion and enhance the occurrence of deprotonated surface aluminols that is consistent with the decrease in surface potential.